Oral Microflora in Dental Diseases (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Infectious diseases of the oral cavity occur due to various pathogens, including bacteria, fungi, and viruses. These diseases affect the mucosa, teeth, gums, and supporting structures, leading to discomfort, pain, inflammation, and in severe cases, systemic complications.